PENGUATAN KAPASITAS ORGANISASI KEPEMUDAAN MELALUI PROGRAM RUANG MUDA SEBAGAI UPAYA PEMBERDAYAAN PEMUDA KOTA PROBOLINGGO - Muhammad Masyhuri; Husni Mubaroq (Jurnal Pengabdian Masyarakat Multidisiplin, 2026)
This Community Service Program (Program Pengabdian kepada Masyarakat/PKM) aimed to enhance the capacity of youth organizations through the Ruang Muda Program as an effort to empower young people in Probolinggo. The program was initiated due to the relatively low managerial capacity, leadership skills, and social participation of youth organizations in regional development. The method employed was the Asset-Based Community Development (ABCD) approach, which emphasizes the utilization of local assets and community potentials through the stages of discovery, dream, design, define-destiny, and evaluation. The activities were conducted over two days in the form of seminars, workshops, leadership training, public speaking training, organizational management training, mentoring sessions, and Focus Group Discussions (FGDs), involving 60 participants from various youth organizations. The results indicated a significant improvement in participants’ capacities, as reflected in the increase in organizational understanding (from 55% to 86%), leadership skills (from 52% to 84%), public speaking abilities (from 48% to 82%), and work-program planning skills (from 45% to 80%). Furthermore, the program contributed to enhancing participants’ self-confidence, communication skills, youth-based development ideas, and inter-organizational collaboration. The social impacts included increased youth participation in social activities and the establishment of stronger collaborative networks among youth organizations in Probolinggo. Therefore, the Ruang Muda Program proved to be an effective model of community-based youth empowerment that is adaptive, participatory, and sustainable.